Super-resolution localization microscopy of γ-H2AX and heterochromatin after folate deficiency - Bach, Margund; Krufczik, Matthias; Cremer, Christoph; Rösl, Frank; Hausmann, Michael (International journal of molecular sciences, 2017)
Folate is an essential water-soluble vitamin in food and nutrition supplements. As a one-carbon source, it is involved in many central regulatory processes, such as DNA, RNA, and protein methylation as well as DNA synthesis and repair. Deficiency in folate is considered to be associated with an increased incidence of several malignancies, including cervical cancer that is etiologically linked to an infection with “high-risk” human papilloma viruses (HPV). However, it is still not known how a recommended increase in dietary folate after its deprivation affects the physiological status of cells. To study the impact of folate depletion and its subsequent reconstitution in single cells, we used quantitative chromatin conformation measurements obtained by super-resolution fluorescence microscopy, i.e., single molecule localization microscopy (SMLM). As a read-out, we examined the levels and the (re)positioning of γ-H2AX tags and histone H3K9me3 heterochromatin tags after immunostaining in three-dimensional (3D)-conserved cell nuclei. As model, we used HPV16 positive immortalized human keratinocytes that were cultivated under normal, folate deficient, and reconstituted conditions for different periods of time. The results were compared to cells continuously cultivated in standard folate medium. After 13 weeks in low folate, an increase in the phosphorylation of the histone H2AX was noted, indicative of an accumulation of DNA double strand breaks. DNA repair activity represented by the formation of those γ-H2AX clusters was maintained during the following 15 weeks of examination. However, the clustered arrangements of tags appeared to relax in a time-dependent manner. Parallel to the repair activity, the chromatin methylation activity increased as detected by H3K9me3 tags. The progress of DNA double strand repair was accompanied by a reduction of the detected nucleosome density around the γ-H2AX clusters, suggesting a shift from hetero- to euchromatin to allow access to the repair machinery. In conclusion, these data demonstrated a folate-dependent repair activity and chromatin re-organization on the SMLM nanoscale level. This offers new opportunities to further investigate folate-induced chromatin re-organization and the associated mechanisms.